William Blake and the Napoleon Factor: Rethinking Empire and the Laocoön Separate Plate - Paice, Rosamund (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2014)
This essay examines a distinct shift in William Blake’s thoughts on empire, and argues that his Laocoön separate plate marks the culmination of his revised views. While Blake initially distinguished negative, commercial and tyrannical forms of empire from positive, non-tyrannical forms of empire that he conceived of as founded upon the arts, he subsequently did away with these distinctions, and came to see an irremediable link between imperial and commercial worlds. By situating Blake’s changing views on empire against the backdrop of the empire-building of Napoleon as it relates to the appropriation of art, this essay clarifies the particular focus on empire and commerce of so many of the Laocoön separate plate’s inscriptions.